Perancangan Aplikasi Kompresi File Gambar Dengan Menerapkan Algoritma Unary Coding - Fitri Wardani Pakpahan (KLIK: Kajian Ilmiah Informatika dan Komputer, 2020)
Image file format bmp is a format developed by microsoft which consists of arrangement of dots (pixels) stored in computer memory. Bmp is an uncompressed image file, so its size is large enough and not appropriate for inadequate memory capacity. One solution to this problem is to reduce the size or compress the image file. With the compression is expected to save costs and time expended in order to increase data storage media facilities on the computer and speed up the data transfer process. The compressed image file uses the Unary Coding algorithm. With the compression of image files, it will be easier for users to reduce image files, and speed up the process of transferring image files and save time spent to increase data storage media facilities on the computer